Interactions of maitotoxin with voltage-sensitive calcium channels in cultured neuronal cells. - Freedman, S B (1984)
The dinoflagellate toxin maitotoxin (MTX) stimulated 45Ca2+ uptake in cultured NG108-15 neuroblastoma X glioma cells. Depolarizing stimuli (e.g., 50 mM K+) produced an immediate stimulation in Ca2+ uptake, whereas that produced by MTX occurred only after a lag period of about 2 min. MTX did not stimulate Ca2+ uptake into fibroblasts. Both 50 mM K+- and MTX-stimulated Ca2+ uptake was blocked by organic calcium channel antagonists (nitrendipine, D-600, diltiazem) at very low concentrations. Cd2+ was also a potent blocker. The novel dihydropyridine BAY K8644 enhanced Ca2+ uptake in the presence of 50 mM K+ but had no effect in 5 mM Ca2+. However, in the presence of MTX, BAY K8644 stimulated Ca2+ uptake in 5 mM K+. The effects of MTX were not blocked by tetrodotoxin but were decreased in Na+-free medium. MTX did not stimulate Na+ uptake into NG108-15 cells and did not alter [3H]nitrendipine binding to rat brain cortical synaptosomes. It is concluded that MTX may alter the voltage dependence of calcium-channel activation.